2008
DOI: 10.1523/jneurosci.4099-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Activation in Astrocytes Protects against Neurodegeneration in Mouse Models of Familial Amyotrophic Lateral Sclerosis

Abstract: Activation of the transcription factor Nrf2 in astrocytes coordinates the upregulation of antioxidant defenses and confers protection to neighboring neurons. Dominant mutations in Cu/Zn-superoxide dismutase (SOD1) cause familial forms of amyotrophic lateral sclerosis (ALS), a fatal disorder characterized by the progressive loss of motor neurons. Non-neuronal cells, including astrocytes, shape motor neuron survival in ALS and are a potential target to prevent motor neuron degeneration. The protective effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
328
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(359 citation statements)
references
References 43 publications
17
328
0
3
Order By: Relevance
“…This observation is consistent with upregulated expression of Nrf2 (nuclear factor, erythroid derived 2, like 2) mRNA in the cerebella of old mutant mice (Fig. 4C), a gene coding for a transcription factor regulating the expression of antioxidant genes (Vargas et al ., 2008). …”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with upregulated expression of Nrf2 (nuclear factor, erythroid derived 2, like 2) mRNA in the cerebella of old mutant mice (Fig. 4C), a gene coding for a transcription factor regulating the expression of antioxidant genes (Vargas et al ., 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a neuropeptide-like hormone, NLP-7, has been recently shown to act downstream of skn-1 to promote life-span extension by dietary restriction (Park et al 2010). It is also interesting to note that astrocyte activation of Nrf2 is sufficient to convey neuronal protection in mouse models of PD and ALS (Vargas et al 2008;Chen et al 2009), demonstrating that Nrf2-dependent neuroprotection in mammals can also be non-cell autonomous. The genetic tools available in C. elegans should allow us to determine to what degree cell autonomous activation of skn-1 contributes to protection against Ab 42 toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Nrf2 activation has been reported to be protective in a mouse MPTP model of PD (Chen et al 2009), as well as a transgenic mouse model of familial amyotrophic lateral sclerosis (ALS) (Vargas et al 2008). Similarly, chemical or genetic activation of the Nrf2 pathway is protective in multiple Drosophila models of PD (Trinh et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…38 On the other hand, a recent study suggested that Nrf2 overexpression in astrocytes significantly delayed onset and extended survival of SOD1-G93A mice. 39 GST secretion by astrocytes has been demonstrated to be protective for neurons against oxidative stress. 40 The Nrf2 gene was genetically depleted from both neurons and astrocytes in the double mutant animals generated in our current study, and the depletion of Nrf2 in the proliferated astrocytes can exacerbate the toxicity to motor neurons and contribute to the deteriorative motor neuron loss in Nrf2 À / À SOD1-G93A mice.…”
Section: Effect Of Nrf2 Knockout On Als Mice Y Guo Et Almentioning
confidence: 99%